Financial Technologies and their Impact on The Development Opportunities of Regional Banks - T. N. Zverkova (Учёт. Анализ. Аудит, 2024)
Digital transformation has led to the emergence of technology-based financial services, known as FinTech, which are rapidly changing traditional banking by penetrating all areas of banking, creating many innovative applications including lending, payments, asset management, etc. The rapid growth of Fintech companies has the potential to become a serious threat to local banks.The purpose of the study is to examine the impact of financial innovations on the activities of regional banks and to consider possible scenarios for the development of the latter in the context of FinTech expansion in the banking market.In the course of the work by applying methods of expert assessments and generalization it was revealed that financial innovations play a decisive role in the development of banking services and improving the quality of customer service. The relevance of the study is due to the need to find possible ways to integrate financial technologies into the activities of local banks —  in the new realities, they should deepen partnerships with FinTech and systematically adjust their strategies, as the digital transformation of business is inevitable.The results obtained —  scenarios substantiating the potential impact of digitalization of FinTech services on banks — can be used to develop development strategies for local banks.